Answer:
y - 0 = -3/4(x - 8)
y = -3/4x + 6
Step-by-step explanation:
Answer:
Multiply vector c by the scalar -1/2.
Step-by-step explanation:
Look at vector c.
It has an x component of 4 and a y component of 4.
You can write vector c as a sum of its components using unit vectors in the x direction (i) and in the y direction (j).
c = 4i + 4j
Now look at vector d, and write it also as a sum of its x and y components.
d = -2i - 2j
Now ask yourself, what operation do I do to 4 to end up with -2?
One answer is to multiply 4 by -1/2.
d = (-1/2)c = (-1/2)(4i) + (-1/2)(4j) = -2i - 2j
That worked. By multiplying vector c by the scalar -1/2, you end up with vector d.
Answer: power of a power
Step-by-step explanation:
in the expression (x^4)^9, 4 and 9 are powers. 9 is the power of x^4, so you have to multiply 4 by 9 to get x^36. this means it's a power of a power